2020
DOI: 10.1155/2020/8861347
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Subchondral Bone and Pain Behavior Changes in a Novel Bipedal Standing Mouse Model of Facet Joint Osteoarthritis

Abstract: Background. The subchondral bone parallels with the progression of osteoarthritis (OA). However, the biomechanical properties and histopathological changes of subchondral bone changes in the lumbar facet joint (LFJ) after long-term axial loading on the spine have not been explored. In this study, we aimed to investigate the subchondral bone histopathological changes that occur in the LFJ and pain behaviors in a novel bipedal standing mouse model. Methods. Sixteen 8-week-old male C57BL/6 mice were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…1 D–G). We further investigated whether cellular senescence also exists in degenerated FJ in mice, we induced FJ degeneration in mice using a bipedal standing model, which significantly increased spinal axial stress, as previously described [ 12 ]. We found that there was no significant difference in the facet joint degeneration of both sides of the standing model mice by HE staining and safranin O staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 D–G). We further investigated whether cellular senescence also exists in degenerated FJ in mice, we induced FJ degeneration in mice using a bipedal standing model, which significantly increased spinal axial stress, as previously described [ 12 ]. We found that there was no significant difference in the facet joint degeneration of both sides of the standing model mice by HE staining and safranin O staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Progressive cartilage degeneration and pain hypersensitivity were observed. Miao Li et al 30 placed the mice in a beaker containing limited water to induce the bipedal standing posture and the LFJ OA was observed at 24 weeks. Due to the differences in anatomy, as described previously, the conclusions of these models do not apply to the cervical spine, and changes in the IVDs of the same segment have not been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to establish a novel animal model to simulate the daily posture of humans to establish the biomechanical loading conditions, because it is an essential step in the effort to explore the pathological changes of FJ degeneration associated with mechanical stress. Here, the current study uses a novel bipedal mouse model, which could simulate human standing postures for a long time (Ao et al, 2019;Li et al, 2020). Using this novel model provides natural positions resembling human beings, and gives researchers a chance to simulate the mechanical loadings in animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to use a bipedal animal model to mimic the standing posture of humans as well as investigate the effects of high-frequency WBV conditions on IVD and FJ. Previous studies demonstrated a novel bipedal mouse model by placing mice in limited water to induce a standing posture for longperiods, and thus directly resulting in IVDD and FJ degeneration (Ao et al, 2019;Li et al, 2020). Here, the aim of the present study is to explore the effects of long-term WBV on the catabolic and anabolic metabolism of IVD and FJ using the novel bipedal mouse model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation